Analiza poziomu i determinant konkurencyjności MŚP w regionie sieradzkim - Przybysz, Zofia; Dopieralska, Magdalena (Wydawnictwo Politechniki Łódzkiej, 2010)
Na konkurencyjność przedsiębiorstw wpływa wiele czynników (np. ceny produktów i usług, jakość produktów i usług, trwałe relacje z klientami, innowacyjny charakter wyrobu/usługi) W artykule przedstawiono analizę wyników badań empirycznych dotyczących konkurencyjności MSP z regionu sieradzkiego.

Many factors influence the competitiveness of enterprises (e.g. prices of products and services, the quality of products and services, stable relations with clients, an innovative character of a product or service). The article presents an analysis of the results derived from empirical research concerning the competitiveness of SMEs from the Sieradz region.
Competitiveness of Small and Medium-sized Enterprises